Sosialisasi Penerapan Kemanan Pangan Pada Produk Minuman dan Makanan di Cafe Gushur Chilin’Space - Sihotang, Siti Fatimah; Elnovreny, Jane; Zuhri; Ridho, Farhan (Publikasi Pengabdian Masyarakat, 2022)
Food safety is a crucial aspect of Sanitary Science because it is an absolute requirement for providing safe and healthy food. Because food safety is an absolute requirement, everyone (despite their socioeconomic status) has the right to access safe and healthy food. Before food or beverages is served, it generally undergoes a processing process either in an industry or in a household. Considering that food and beverages must be available at all times, while the population is increasing, this situation requires us to improve and accelerate food supply through the correct supply chain. This condition has been clarified by the number of SMEs (Small and Medium Enterprises) that have sprung up in the food and beverage sector, especially in Medan City. One of them is Gushur Chillin Space Cafe'. Therefore, knowledge about food preservation, food additives, food sanitation and hygiene plus everything related to food safety is crucial and needs to be informed to entrepreneurs, cafe' employees and other SMEs engaged in the food and beverages industry. This research is a literature study. The results of the community service activities indicated that the participant's knowledge of the application of food safety increased, and they got an idea of how to serve food and beverages that were guaranteed to be safe in terms of ingredients and processes for consumers. The other results of the increasing knowledge about food safety are the participant could market their business more widely and be known by the public.